Acceptability Towards Human Milk Banking Among Postnatal Mothers in a Tertiary Level Hospital, Nepal - Poudel, Smriti; Thakulla, Bindu; Maharjan, Punam; Prajapati, Laxmiswori (Medical Journal of Eastern Nepal, 2025)
Background Breast milk is the optimal food for infants, offering numerous health benefits. When a mother’s milk is unavailable, the World Health Organization recommends donated human milk as the best alternative. Although there is considerable research on the safety and scientific aspects of donor milk, Nepal having only one certified Human Milk Bank, its utilization is limited. Besides, fear of disease transmission, cultural, and religious prohibitions as well as concerns about the inadequacy of MOM for the babies of donor mothers and safety concerns are the factors to be addressed for the development of interventions to address identified barriers. Methods A descriptive, quantitative, cross-sectional study was conducted among 181 postnatal mothers at a tertiary hospital in Kathmandu using non-probability purposive sampling technique. Ethical approval was obtained from the IRC (PMWH-IRC-65/1816) of Paropakar Maternity and Women’s Hospital. Data were collected from 2081/10/20 (02/02/2025) to 2081/ 12/20 (02/04/2025) via a self-developed structured interview schedule and analysed using descriptive and inferential statistics (SPSS version 20). Results The study revealed that only 5% of the participants had adequate knowledge of human milk banking. However, 85.6% expressed acceptability towards human milk banking. Knowledge level was significantly associated with education, residential area, and income (p<0.001) whereas, acceptability was significantly associated with ethnicity (p<0.001). A positive correlation (r=0.392, p<0.001) existed between knowledge and acceptability. Conclusion The study finding shows low level of knowledge but high acceptability toward human milk banking. Education, residence, and income influenced knowledge levels whereas ethnicity of the respondents influenced acceptability. Awareness campaigns and educational programs are recommended to improve understanding.